Analysis of Digital Content that Captures Gen Z Interest in Marketing Campaigns - Sani, Siti Enjang Amanah (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This study addresses the challenges brands face in understanding Gen Z’s preferences for digital content amidst the ever-evolving landscape of social media. The aim of this research is to identify key elements in digital content that capture Gen Z’s attention and understand the reasons behind their interest, helping brands design effective and relevant marketing campaigns for this generation. This study uses a qualitative descriptive method to analyze digital content on Instagram posted by various brands, focusing on Gen Z's preferences regarding visual elements, delivery style, and interactivity. Data was collected through direct observation of brand Instagram accounts and analyzed using content analysis to identify patterns in Gen Z’s preferences for engaging content. The findings indicate that marketing campaigns targeting Gen Z succeed in capturing attention through authentic storytelling, interactive visual content, and effective use of social media platforms. This approach fosters emotional engagement and positive responses from Gen Z toward the brand.